2016
DOI: 10.1182/blood.v128.22.816.816
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Secreting CAR T Cells Enhance Cell Persistence, Induce Prolonged B Cell Aplasia and Eradicate CD19+ Tumor Cells without Need for Prior Conditioning

Abstract: Chimeric antigen receptor (CAR) T cell therapy has consistently shown significant results against acute lymphoblastic leukemia (ALL) in clinical trials1. However, results with other hematological or solid malignancies have been far more modest2. These disparate outcomes could be partially due to an inhibitory tumor microenvironment that suppresses CAR T cell function3. Thus, in order to expand the anti-tumor CAR T cell applications, a novel strategy in which these cells are capable of overcoming the hostile tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…And lastly, as CARs have been demonstrated to persist in humans for years post-infusion 34 , the ability to recall resident convertibleCAR-Ts to attack primary or secondary malignancies (either with the original targeting MicAbody or a different one) without having to reengineer or generate a new batch of CAR cells should be highly advantageous. Unlike scenarios where CARs have been engineered to constitutively express cytokines 35,36 , delivery of cytokines exclusively to convertibleCAR-T cells can be modulated depending upon the manufacturing or clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…And lastly, as CARs have been demonstrated to persist in humans for years post-infusion 34 , the ability to recall resident convertibleCAR-Ts to attack primary or secondary malignancies (either with the original targeting MicAbody or a different one) without having to reengineer or generate a new batch of CAR cells should be highly advantageous. Unlike scenarios where CARs have been engineered to constitutively express cytokines 35,36 , delivery of cytokines exclusively to convertibleCAR-T cells can be modulated depending upon the manufacturing or clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…39 We have explored strategies to overcome CLL-mediated immune resistance in mouse models by further modifying CAR T cells to constitutively express an additional costimulatory ligand (e.g., 4-1BBL, CD40L) or to secrete immunoregulatory cytokines (e.g., IL-12, IL-18), and a phase I clinical trial of 19-28z/4-1BBL CAR T cells in patients with R/R CLL is ongoing at our institution. [40][41][42][43][44][45] Several other clinical investigations are ongoing to combine immunologic checkpoint blockade or the oral Bruton's tyrosine kinase (BTK) inhibitor ibrutinib based on preclinical and preliminary clinical evidence showing that ibrutinib can enhance T cell proliferation, decrease PD-1 and CD200 expression, and increase skewing of the central memory phenotype of CAR T cells. 12,16,32,39,46 In summary, administration of 19-28z CAR T cells to patients with residual CLL following initial chemoimmunotherapy with PCR was safe and well tolerated, and a subset of patients achieved a meaningful clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Avanzi et al, have developed CAR T cells that constitutively secrete IL-18. Their results revealed that IL-18 not only can enhance CAR T cell survival and antitumor activity both in vitro and in vivo, but also can activate cells of endogenous immune system in immunocompetent mice (37). In a similar study, Hu et al, discovered that anti-CD19 and antimesothelin CAR T cells engineered to secrete IL-18 not only can support in vivo engraftment and persistence of CAR T cells but also enhance secretion of IFN-γ and several other cytokines such as IL-2, G-CSF, GM-CSF, TNF-α, IL-17A, and IP-10 (38).…”
Section: Manipulating Car T Cells To Express Cytokines and Their Recementioning
confidence: 99%